Necrotizing Fasciitis Complicating Pregnancy: A Case Report and Literature Review - Marinos Nikolaou; Petros Zampakis; Vasiliki Vervita; Konstantinos Almaloglou; Georgios Adonakis; Markos Marangos; Georgios Decavalas (Case Reports in Obstetrics and Gynecology)
Necrotizing fasciitis is a rare, life-threatening surgical infection in pregnancy with high rates of morbidity and mortality. A 15-year-old primigravid woman, at 28 weeks of gestation with no significant previous medical history, was admitted to our hospital complaining of severe left lower extremity pain and high fever the last 72 hours. During clinical examination, she had a swollen, erythematous and tender to palpation inflamed skin over the medial aspect of the upper thigh without any evidence of injury. Incision drainage was performed immediately and she received broad spectrum antibiotics. During initial laboratory examinations, diabetes mellitus was diagnosed. There was no clinical improvement over the following days. Magnetic resonance imaging (MRI) revealed subcutaneous tissue inflammation and edema of infected tissues confirming the disease entity. Multidisciplinary therapy with immediate aggressive surgical debridement of necrotic tissues, multiple antibiotics, and intensive care monitoring was performed successfully. The patient’s postoperative course was uncomplicated and skin defect was closed with split thickness skin grafting. Our case emphasized the potential immunosuppressive role of pregnancy state in conjunction with diabetes mellitus in the development of severe necrotizing soft tissue infections.